Hydrothermal synthesis of TiO2/reduced graphene oxide nanocomposite with enhanced photocatalytic activity. (1st December 2014) - Cheng, Guoe; Zhang, Yu; Ke, Hanzhong; Hao, Tingting; Wang, Youzhi
Abstract : The composite of peanut‐like TiO2 nanoparticles and reduced graphene oxide (rGO) was successfully synthesised via a facile one‐step hydrothermal method in mixed solvents of diethanol amine and distilled water. The crystallite, morphology and structure features of the composite were characterised by X‐ray diffraction, Brunauer‐Emmett‐Teller specific area analysis, transmission electron microscopy and high‐resolution transmission electron microscopy. The results indicated that the as‐synthesised TiO2 was of peanut‐like shape with about 21–32 nm in length and was anchored on the surface of the rGO sheet. In addition, the TiO2 /rGO composite presented excellent photocatalytic activity of rhodamine B under visible light irradiation compared with commercial Degussa P25. A proposed mechanism for the photocatalytic process is also discussed.